Some aspects of seed infection and control of the collar-rot complex of peas (Pisum sativum L.), caused by Mycosphaerella pinodes (Berk. and Blox.) Vestergr., Phoma Medicaginis var. pinodella (Jones) Boerema and Ascochyta pisi Lib. : a thesis presented in partial fulfilment of the requirements for the degree of Masterate of Agricultural Science. - Hor, Yue Luan (Massey University, 1972)
The green pea, Pisum sativum L., is one of the principal field crops in New Zealand (Anon, 1970a), and essentially two varieties, P. sativum var. sativum (garden peas) and P. sativum var. arvense (field peas) are grown. Peas of the garden variety are used for human consumption and may be consumed fresh, processed or marketed as split peas. The field variety is mainly used for animal consumption. However both varieties are widely grown for seed production and are important to New zealand in international seed trade. The cultivation of green peas in New Zealand has increased steadily over the last few years. In 1966-67 approximately 28,000 acres were sown, while in 1968-69 this had increased to approximately 50,000 acres (Anon, 1970a). The main pea producing areas are Canterbury, Wellington, Marlborough, Hawkes Bay and Otago, with Canterbury alone being responsible in 1967-68 for three-quarters of the total production in New Zealand (Anon, 1969). In 1968-69 export of seed peas and artificially dehydrated peas alone resulted in total earnings of more than two million dollars (Anon, 1970b). [From Introduction]
Keywords: Peas; Diseases and pests